The effect of chosen parameters of a telephone channel on voice identification - Czesław BASZTURA; Wojciech MAJEWSKI (Archives of Acoustics)
The method and results of investigations aimed at the evaluation of the effect of chosen parameters of a telephone channel on the masking of the individual voice features are presented. In the experiments on voice samples of 10 speakers (men) a speech signal was represented by the amplitude correlation matrix and the distribution of time intervals between the zero-crossings of the speech signal. The effect of the frequency band of a telephone channel and of distortions determined by different signal to noise ratios on the probability of correct voice identification was investigated. The results obtained show the possibility of voice identification under the conditions of telephone transmission provided some definite values of the parameters of a telephone link are maintained.